(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Since the first laparoscopic cholecystectomy (LC) in 1985, there has been much advancement in laparoscopic surgery in terms of reduction in number and size of ports. We report a new technique of performing mini laparoscopic cholecystectomy using only three ports, 5 mm each. The indications of this procedure include GB polyps, GB dyskinesia, microlithiasis, and idiopathic pancreatitis